PENGARUH PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN TOYOTA YARIS PADA PT. NASMOCO GOMBEL SEMARANG - Perwira, Faber Tri; Prihartini, Apriatni Endang; Wijayanto, Andi (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2013)
The purpose of this study is to investigate and examine the effect of product, price, and promotion to the Toyota Yaris purchasing decisions on PT. Nasmoco Gombel Semarang. This study uses explanatory research approach to the 94 respondents who were taken by purposive sampling method.Techniques of data collection using questionnaires, interviews, and documentation. The data obtained were analyzed using linear regression analysis. Based on the results of analysis variables influence product purchasing decision variable at 64.9%. Variables affect the price of the purchase decision variable of 93.3%. Promotion variable influence on purchase decisions 74.8%. Taken together the variables of product, price and promotion influence on purchase decisions of 94.9%. The better the product, the price is cheap, and attractive promotions then the higher the purchasing decision. Suggestion for the company, the company should keep perform periodic evaluation and improvement so that the product in the eyes of consumers better than other similar products. Companies must keep a decent price for the consumer that is based on income levels and competition, keep frequent and interesting promotion